The effects of lower extremity muscle strength characteristics on grab and track start performance in young competitive swimmers - Argun, B.; Demirci, N.; Umutlu, G. (Isokinetics and Exercise Science, 2023)
BACKGROUND: Limited data exist regarding segmental contributions of lower extremity muscles to the swim start performance during different start techniques in young swimmers. OBJECTIVE: To determine the differences in the kinematic parameters between the grab start (GS) and track start (TS) techniques and assess the interactions between the lower limb muscle strength and swim start performance. METHODS: A total of 40 swimmers, 20 girls (age: 13.70 ± 1.80 y, height: 161.65 ± 8.28 cm, body weight: 53.70 ± 8.65 kg) and 20 boys (age: 13.90 ± 1.45 y, height: 160.95 ± 12.70 cm, body weight: 52.95 ± 12.64 kg), 13-16 y of age, at the competitive level were recruited. Ankle, hip, and knee muscles were tested isokinetically at 60°/s and the tests were spread over 24 h to avoid fatigue. Several elements relating to GS and TS were measured using a motion pick-up video camera. RESULTS: The angle of entry (EA) at water and knee joint angle (KA) were significantly greater during GS both for boys (EA: 44.18 ± 1.07° vs. 43.03 ± 1.28°; KA: 112.10 ± 15.25° vs. 107.21 ± 21.13)° and girls (45.09 ± 1.28° vs. 43.36 ± 1.55°; KA: 103.08 ± 11.21° vs. 97.45 ± 19.52°, p< 0.05). Flight time (FT), flight distance (FD), KA, and flight velocity (FV) were significantly higher for boys both during GS and TS, whereas EA was significantly lower for boys during GS compared to girls (p< 0.05). Lower limb strength performance was positively significantly correlated with FT, FD, and FV both during GS and TS (p< 0.05). Hip muscle strength was inversely correlated with the EA both during GS and TS (p< 0.05). The combination of the knee, ankle, and hip extensor and flexor muscle strengths had a greater effect during GS (35% vs. 29%) in RT, (48% vs. 46%) in FT, (59% vs. 57%) in FD, and (63% vs. 57%) in FV compared to the TS. CONCLUSIONS: Incorporating lower body strength training into the swimming training schedule may improve swim start performance variables during grab start and track start techniques.